Turkey’s Israel policy in the post-Cold War period :|the struggle of identity over realpolitik - Nasi, Selin. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This study offers a neoclassical realist analysis of Turkey’s post-Cold War Israel policy. By looking at both foreign and domestic developments, this study analyzes the course of Turkish-Israeli relations from a historical perspective, with the aim of identifying elements of continuity and change, while it also sheds light onto the contradictory forces at play in shaping Turkey’s Israel policy, at the systemic and unit levels. As such, it argues that the institutional foundations along with common threat perceptions that facilitated a strategic partnership between Turkey and Israel in the 1990s, began to erode, in part due to changes in the structure of the international system as well as domestic political developments in the 2000s. Against a backdrop in which Ankara has perceivably shifted its strategic orientation away from the West, this study asserts that Turkey’s Israel policy has been marked by a struggle between realpolitik and identity, in which, the former encourages cooperation between the countries while the latter drives them further apart.